Plan de negocios para la creación de una crepería móvil en la ciudad de Quito - Armendáriz Pachar, Luis Eduardo (2012)
Now days, consumers are looking for a healthy diet, taking more and more food with adequate nutritional properties, so that contributes to improving the health and welfare or to reduce the risk of diseases. In addition, college students and workers in public and prívate companies have little time to feed, because of their daily activities. Therefore, "La Crepe" was born with the idea of offering healthy products ready to be eaten with innovation and comfort. lt seeks to offer an alternative service of food to students and working people, who are those that spend a longer time outside their homes, so they frequently consumed food in restaurants, cafeterías, and minimarkets . This group of people has a very short time to eat healthy. On the other hand, most places that prepare food close to universities and public and private institutions, do not prepare their food with a quality standard and hygiene requirements. La Crepe is an innovative idea, non-usual; offering an alternative form for feeding and in its main feature is the easiness of switching from one location to another depending on demand. By design, it can offer both sweet and salt crepes, with different ingredients, according to the tastes and preferences of consumers . Additionally, this type of business in Ecuador has not been exploited; becoming a great business opportunity in the future that can be franchised .